Analisis Fungsi Bahasa Geoffrey Leech dalam Indang Nagari Muaro Paneh - AS, Fadly (Universitas Muhammadiyah Surabaya, 2024)
The objective of this article is to identify the linguistic forms and meanings of language in indang lyrics in Muaro Paneh village and to determine their function. This study employs descriptive qualitative research methods using observation and documentation as the data collection techniques. The manuscript of the indang lyrics collection in Muaro Paneh village is the primary source for the data. The analysis method utilises Wijana's speech act type theory, incorporating seven kinds of meaning and five language functions as per Leech. The types of speech acts identified are: direct literal, direct non-literal, indirect literal, and indirect non-literal. The types of meaning identified include conceptual, connotative, social, affective, and reflective. The language functions identified are: informational, expressive, directive, aesthetic, and phatic. Non-literal connotative meanings with a directive function are found in most of the texts of the indang Muaro Paneh village. It serves as an instrument of social control over people's lives as oral literature.